Cognitive Orientation to daily Occupational Performance (CO-OP): A New Approach for Children with Cerebral Palsy. (15th March 2017) - Cameron, Debra; Craig, Tammy; Edwards, Brydne; Missiuna, Cheryl; Schwellnus, Heidi; Polatajko, Helene J.
ABSTRACT: Aims: The results of a small single-case study series suggested that Cognitive Orientation to daily Occupational Performance (CO-OP) may be a successful approach for children with cerebral palsy (CP). Therefore a pilot randomized controlled trial was conducted with the following research questions—is CO-OP a feasible approach to use with children with CP, what are the effects of CO-OP when compared to usual practice, and is a larger study warranted? Methods: 18 children between age 7 and 12 (nine in CO-OP group and nine in Current Usual Practice Approach (CUPA) group) received ten 1-hour sessions of intervention on average once per week at home. Primary outcome measures were the Canadian Occupational Performance Measure and the Performance Quality Rating Scale (PQRS). PQRS assessors were blind to group allocation and timing of assessment. Results: All children in the CO-OP group were able to learn the strategies and achieve their chosen goals, thus demonstrating the feasibility of the approach. Both approaches equally promoted skill acquisition and skill maintenance at follow-up. Effect sizes suggest that CO-OP may show some advantage for transfer and maintenance. Conclusion: Based on these initial findings, further research is warranted.